Revisiting the concentration observations and source apportionment of atmospheric ammonia - Pan, Yuepeng; Gu, Mengna; He, Yuexin; Wu, Dianming; Liu, Chunyan; Song, Linlin; Tian, Shili; Lü, Xuemei; Sun, Yang; Song, Tao; Walters, Wendell W.; Liu, Xuejun; et al. (Springer, 2020)
While China’s Air Pollution Prevention and Control Action Plan on particulate matter since 2013 has reduced sulfate significantly, aerosol ammonium nitrate remains high in East China. As the high nitrate abundances are strongly linked with ammonia, reducing ammonia emissions is becoming increasingly important to improve the air quality of China. Although satellite data provide evidence of substantial increases in atmospheric ammonia concentrations over major agricultural regions, long-term surface observation of ammonia concentrations are sparse. In addition, there is still no consensus on whether agricultural or non-agricultural emissions dominate the urban ammonia budget. Identifying the ammonia source by nitrogen isotope helps in designing a mitigation strategy for policymakers, but existing methods have not been well validated. Revisiting the concentration measurements and identifying source apportionment of atmospheric ammonia is thus an essential step towards reducing ammonia emissions.